2005
DOI: 10.1063/1.1861959
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between low-field microwave absorption and magnetoimpedance in Co-based amorphous ribbons

Abstract: Microwave power absorption measurements at 9.4 GHz were carried out on as-cast amorphous ribbons of nominal composition Co66Fe4B12Si13Nb4Cu. Two absorptions were observed: a small signal at a low dc field (<0.01T) and another one at a high dc field (∼0.1682T). The high-field signal shows all the features corresponding to ferromagnetic resonance. The low-field absorption (LFA) signal exhibits different characteristics such as hysteresis and a minimum in power absorption at zero magnetic field. A correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 14 publications
3
67
2
Order By: Relevance
“…This indicates that the LFMA has microwave absorption minimum at zero field in contrast to the microwave absorption maximum for the FMR line at its resonance field. This is similar to the LFMA in Co-based ribbons as reported by Montiel et al [8]. LFMA is understood to be connected to the magnetization processes that occur at applied low field.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…This indicates that the LFMA has microwave absorption minimum at zero field in contrast to the microwave absorption maximum for the FMR line at its resonance field. This is similar to the LFMA in Co-based ribbons as reported by Montiel et al [8]. LFMA is understood to be connected to the magnetization processes that occur at applied low field.…”
Section: Resultssupporting
confidence: 65%
“…Montiel et al have reported a strong correlation between LFMA and giant magneto impedance (GMI) phenomenon mostly in Co-based amorphous ribbons [8]. By using complex Poynting vector Alvarez et.al [15] showed a theoretical correlation between LFMA and magneto impedance (MI) as given by the following relationship.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent results show [18] that as frequency increases (in the 200 MHz -6 GHz range for Co-rich amorphous ribbons), a divergence in the MI response appears with two maxima in the impedance response, corresponding to ±H K (the value of which remains virtually constant at all frequencies), and the FMR response, which becomes field dependent, with a Larmor relation that depends on the geometry of the sample. FMR experiments in Co-rich amorphous ribbons at even higher frequencies (X-band at 9.4 GHz) have exhibited both signals clearly resolved [19], the non-resonant low-field absorption (LFA) similar to MI at fields lower than 50 Oe, and the expected FMR absorption at 1,682 Oe. Therefore our present results show the beginning of this separation.…”
Section: Experimental Results and Modelingmentioning
confidence: 99%